Morphological specializations of the epidermis of an angler catfish Chaca chaca (Siluriformes, Chacidae) in relation to its ecological niche: A scanning electron microscopic investigation. Issue 5 (19th January 2018) - Mistri, Arup; Kumari, Usha; Mittal, Swati; Mittal, Ajay Kumar
Abstract: The present work was undertaken with the aim to deduce morphological adaptations in skin of an angler catfish Chaca chaca by means of scanning electron microscopy. The fish is nocturnal, bottom dwelling, sluggish, ambush predator, lives in sand, mud, or soft substrates often buried and camouflaged for protection and to feed. The surface of the epidermis is covered with polygonal epithelial cells, each having surface relief of microridges forming intricate patterns. In between epithelial cells irregularly distributed mucous cell openings, randomly distributed epidermal specialized structures, taste buds, and neuromasts are discernible. The epidermal specialized structures are keratinized. These are either irregularly the rounded elevated plaque like or the cone shaped structures. The superficial keratinized cells could frequently be discernible exfoliated at the surface. At intervals, characteristic epidermal projections could be observed. Surface of these projections at intervals is differentiated into short stumpy protuberances, each bearing a taste bud at its summit. Further, near the basal portion of these epidermal projections, conical, or rounded plaque like epidermal specialized structures are also discernible. The surface sculpture of the skin of Chaca chaca is associated with the structural and functional significance and physiological adaptations of the epidermis with respect to its ecological niche. Abstract : Surface sculpture of epidermis of Chaca chaca showing epidermal specialized structures, taste buds and neuromasts. Presence of elongated neuromasts is indeed unusual. Elongated epidermal projections on the surface are reported for the first time.